Biomechanical comparison of subsidence performance among three modern porous lateral cage designs. (October 2022) - Yee-Yanagishita, Christian; Fogel, Guy; Douglas, Brooke; Essayan, Gregory; Poojary, Brijesh; Martin, Nicholas; Williams, Gregory M.; Peng, Yun; Jekir, Michael
Abstract: Background: Cage subsidence remains a major complication after spinal surgery. The goal of this study was to compare the subsidence performance of three modern porous cage designs. Methods: Three porous cages were evaluated: a porous titanium cage, a porous polyetheretherketone cage and a truss titanium cage. Mechanical testing was performed for each cage per the American Society for Testing and Materials F2077 and F2267 standards to evaluate cage stiffness and block stiffness, and per a novel clinically relevant dynamic subsidence testing method simulating cyclic spine loading during 3-months postoperatively to evaluate the subsidence displacement. Findings: The porous polyetheretherketone cage demonstrated the lowest cage stiffness (21.0 ± 1.1 kN/mm), less than half of both titanium cages (truss titanium cage, 49.1 kN/mm; porous titanium cage, 43.6 kN/mm). The block stiffness was greatest for the porous titanium cage (2867.7 ± 105.3 N/mm), followed by the porous polyetheretherketone (2563.4 ± 72.9 N/mm) and truss titanium cages (2213.7 ± 21.8 N/mm). The dynamic subsidence displacement was greatest for the truss titanium cage, which was 1.5 and 2.5 times the subsidence displacement as the porous polyetheretherketone and porous titanium cages respectively. Interpretations: Specific porous cage design plays a crucial role in the cage subsidence performance, to a greater degree than the selection of cage materials. A porous titanium cage with body lattice and microporous endplates significantly outperformed a truss titanium cage with a similar cage stiffness in subsidence performance, and a porous polyetheretherketone cage with half of its stiffness. Highlights: Three novel porous cage designs were tested for subsidence performance. The porous titanium cage showed the least amount of subsidence displacement. Cage design plays a greater role in the cage subsidence performance than material.